Self-Configurable Wireless Automatic Irrigation System - Penha, César (2019)
Agriculture in general and landscaping in particular remain as activities in which the amount of wasted water persists at very high levels. Despite all the technology available today, it is still common to find parks and green spaces where the applied irrigation systems are frequently triggered with dubious need. Currently, most irrigation systems are operated manually or are based on pre-defined controlled systems. Internet of Things, can help in information gathering, decision making, obtaining data through sensing, and giving feedback. This article presents an approach to develop a self-reconfigurable wireless automatic irrigation system. Two main contributions are proposed: (1) the development of the prototype of a wireless automatic irrigation system, supporting the automatic verification and selection of sensor devices, based on the required type of sensor and its respective received signal strength indicator and (2) the use of a graphical modelling formalism for the definition of rules that specify the desired irrigation behavior, allowing the automatic generation of code for microcontrollers. The system detects various environmental and soil parameters to optimize water consumption and automate irrigation control at a reduced cost. A proof of concept prototype is presented.